A new species of Carnoya Gilson, 1898 (Rhigonematida: Carnoyidae) parasite of a spirobolid (Diplopoda: Spirobolida) from Cuba - Rodríguez, Nayla García; Rodríguez, Jans Morffe (Zootaxa, 2014)
Carnoya isabelica n. sp. is described parasitizing Nesobolus piedra from Eastern Cuba. The new species is characterized by the presence of 13 copulatory papillae in males (the post-cloacal arranged in two trios, with two lateral papillae and one median papilla that can be laterally displaced), the presence of collars of spines in the both sexes and females with 23–25 collars of spines, cephalic end not swollen and lateral alae extending from the end of spines to the base of the tail. SEM images of both sexes are given.